2008
DOI: 10.1029/2008gl035146
|View full text |Cite
|
Sign up to set email alerts
|

An extensive western Mediterranean deep water renewal between 2004 and 2006

Abstract: The deep waters of the western Mediterranean are known to have an almost constant trend towards higher salinity and temperature values since the 1950s. Recent observations have shown an acceleration of this tendency, which has been attributed by some authors to the effect of the propagation of the signal of the Eastern Mediterranean Transient, from east to west. From 2004 to 2006 five basin‐scale oceanographic cruises evidenced a relevant change in the deep structure of the western Mediterranean. In less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
212
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(243 citation statements)
references
References 24 publications
22
212
4
1
Order By: Relevance
“…The system of deep convection in the Gulf of Lions had a particularly intense event observed during winter of 2005 (López-Jurado et al, 2005;Canals et al, 2006;Schroeder et al, 2008) and to a lesser extent during the following years, when the convection occurred over a much larger and deeper area than usual. This intense formation of dense water in the Gulf of Lions has already been simulated by (Beuvier et al, 2012a(Beuvier et al, ) et al (2012a with the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The system of deep convection in the Gulf of Lions had a particularly intense event observed during winter of 2005 (López-Jurado et al, 2005;Canals et al, 2006;Schroeder et al, 2008) and to a lesser extent during the following years, when the convection occurred over a much larger and deeper area than usual. This intense formation of dense water in the Gulf of Lions has already been simulated by (Beuvier et al, 2012a(Beuvier et al, ) et al (2012a with the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the next 10 years (ARPERA forcing during 1965(ARPERA forcing during -1974 are continuously repeated until 1975 to drive our offline simulations of both passive tracers from 1951 (beginning of the simulation) until 1975. That forcing period was selected because it does not include intense events like the EMT or the WMT (Schroeder et al, 2008); we thus considered this period as best suited to produce reasonable circulation fields for the Mediterranean Sea (Beuvier et al, , 2012bBeuvier, 2011). Then to complete the offline 3 H-3 He simulations, we applied the NEMO-MED12 circulation fields corresponding to the remaining 1975-2011 period forcing.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrated the importance of the good representation of the atmospheric synoptic chronology linked with the so-called weather patterns or weather regimes Papadopoulos et al, 2012;Durrieu de Madron et al, 2013) or with the passage of Mediterranean storms associated with strong airsea exchanges (Herrmann and Somot, 2008;Herrmann et al, 2010). At a longer timescale, interannual to decadal variability of the atmospheric forcings (water or heat fluxes) is known to dominate the climate variability of the deep water mass formation in both basins of the Mediterranean Sea Herrmann et al, 2010;L'Heveder et al, 2013), leading sometimes to exceptional decadal events such as the Eastern Mediterranean Transient (Roether et al, 2007) or the Western Mediterranean Transition (Schroeder et al, 2008).…”
Section: Hamon Et Al: Design and Validation Of Medrys A 1992-201mentioning
confidence: 99%
“…The observed massive dense water input from the Aegean Sea and Sea of Crete in the early 1990s is known as the Eastern Mediterranean Transient (EMT) event (Roether et al, 1996;Klein et al, 1999;Lascaratos et al, 1999). The extensive deep water formation in the western Mediterranean Sea (WMed) between 2004 and 2006, known as the Western Mediterranean Transition (WMT) event (Schroeder et al, 2008(Schroeder et al, , 2010, is thought to have been triggered by the EMT event . Nevertheless, both events are part of a general circulation pattern which can be observed in the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%